Gastrointestinal Tract Microbiome Dynamics Following Treatment with SER-109, an Investigational Oral Microbiome Therapeutic to Reduce the Recurrence of Clostridium difficile Infection (CDI). (4th October 2017) - Henn, Matthew; Ford, Christopher; O'Brien, Edward; Wortman, Jennifer; Simmons, Sheri; Diao, Liyang; Litcofsky, Kevin; Bernardo, Patricia; Aunins, John; Cook, David; Trucksis, Michele
Abstract: Background: Recurrence of CDI occurs within a few weeks after treatment due to antibiotic-induced dysbiosis. SER-109, an investigational, first-in-class microbiome drug, was designed to sustain a clinical response through microbiome restoration with a purified ecology of spores. In an open-label Phase 1b (Ph1b) trial of SER-109 for prevention of recurrent CDI, 26 of 30 subjects did not recur following treatment. In a Phase 2 (Ph2) double-blind controlled trial of SER-109 ( n = 59) vs. placebo ( n = 30), no significant difference was observed in the proportions of subjects with recurrence (44.1% vs. 53.3%, respectively). Here we contrast gut microbiome changes among subjects in both trials to understand differences in clinical outcomes observed 8-weeks after dosing. Methods: We used 16S v4 and high-resolution whole metagenomic shotgun (WMS) sequencing to characterize microbiome changes from stool samples collected at baseline and 1, 4, and 8 weeks post-treatment. Microbiome analyses focused on subjects diagnosed with recurrence via EIA toxin testing (high confidence recurrence; HCR). Results: Significantly greater richness of commensal spore-former species was observed in Ph2 subjects treated with SER-109 compared with PBO at weeks 1 and 4 post-treatment (Mann–Whitney P = 0.008, P = 0.044 respectively) consistent with drug engraftment. In addition, the number of spore-forming species at 1 week post-treatment was significantly greater in non-recurrent subjects vs. HCR subjects (Mann–Whitney P = 0.011). Furthermore, we identified 10 spore-former species that were significantly more prevalent in both SER-109 and non-recurrent subjects (Fig 1). In comparison to Ph1 subjects, SER-109 engraftment was significantly reduced and delayed among Ph2 subjects at all time points (Fig 2). Moreover, Ph1b subjects who received higher doses of SER-109 than that used in Ph2 had increased levels of engraftment. Conclusion: In patients with recurrent CDI and dysbiosis, a focused spore-based therapeutic approach leads to engraftment of SER-109 strains. In addition, microbiome signatures of engraftment were associated with a favorable clinical outcome. Although SER-109 was biologically active, a higher dose may improve the rate and degree of microbiome repair. Disclosures: M. Henn, Seres Therapeutics: Employee and Shareholder, Salary and Stock Options; C. Ford, Seres Therapeutics: Employee and Shareholder, Salary and Stock Options; E. O'Brien, Seres Therapeutics: Employee and Shareholder, Salary and Stock Options; J. Wortman, Seres Therapeutics: Employee and Shareholder, Salary and Stock Options; S. Simmons, Seres Therapeutics: Employee and Shareholder, Salary and Stock options; L. Diao, Seres Therapeutics: Employee and Shareholder, Salary and Stock; K. Litcofsky, Seres Therapeutics: Employee and Shareholder, Salary and stock options; P. Bernardo, Seres Therapeutics: Employee and Shareholder, Salary and Stock options; J. Aunins, Seres Therapeutics, Inc.: Employee and Shareholder, Salary and Stock options; D. Cook, Seres Therapeutics: Employee and Shareholder, Salary and Stock Options; M. Trucksis, Seres Therapeutics Inc.: Employee and Shareholder, Salary and stock options